The Effect of Non-Current Liabilities, Cash Flow and Revenue Growth on Profitability and the Impact on Company Value - Muhammad Alif Widodo; Sri Handayani; Zaenal Abidin (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The COVID-19 pandemic has had a profound impact on the global and national economy, particularly in the aviation industry, disrupting financial performance and company value. This study aims to analyze The Effect of Non-Current Liabilities, Cash Flow, and Revenue Growth on Profitability and the Impact on Company Value using a quantitative approach. Financial data from PT Angkasa Pura I and PT Angkasa Pura II from 2014 to 2023 were examined, and path analysis was conducted using SPSS software. The findings reveal that non-current liabilities have a significant impact on both profitability and company value, whereas cash flow and revenue growth do not show a significant effect. Furthermore, profitability plays a crucial role in enhancing company value. Mediation analysis indicates that profitability significantly mediates the relationship between non-current liabilities and company value, while it does not mediate the effect of cash flow and revenue growth on company value. These findings provide valuable insights for financial decision-making in the aviation sector, emphasizing the importance of managing liabilities effectively to enhance profitability and overall company value.